Formation of cellulose-carbene complex via depolymerization in ILs: Dependence of IL types on kinetics, conformation and dispersity. (1st March 2017) - Ahn, Yongjun; Song, Younghan; Kim, Hyungsup; Kwak, Seung-Yeop
Highlights: Acidic hydrolysis of cellulose was observed using different types of ionic liquids. Anion basicity strongly influenced acid and carbene formation. Carbene was easily reacted with reducing ends of cellulose oriented from hydrolysis. Carbene-cellulose complex induced positive charge on surface of cellulose particle. Induced charge resulted in dispersity improvement of particles. Abstract: This study focused on the influence of anion type on the depolymerization and its effect on the molecular state, dynamics and dispersity of cellulose. GPC and the van Gurp-Palmen plot showed that molar mass was more significantly decreased by 1-butyl-3-methylimidazolium chloride ([C4 C1 Im][Cl]) comparing to 1-butyl-3-methylimidazolium acetate ([C4 C1 Im][OAc]). Acid-catalyzed hydrolysis of cellulose in IL was proved using base titration which was monitored by conductivity and pH value. On the contrary to the depolymerization case, [C4 C1 Im][OAc] solution needed more base to be neutralized than [C4 C1 Im][Cl] solution. The generated carbene was combined with reducing ends of cellulose, which was facilitated in low molar mass consisting of a large number of reducing ends. The formation of cellulose-carbene substitution caused steric hindrance of cellulose chain, thus resulting in increased segmental friction with high molecular density. The cellulose particle combined with carbene can be dispersed stably in aqueous media.